Youtube Learning Media as an Effort to Increase Energy Resources Online Learning Outcomes for Class IV Students - Diah Retnasari (Universitas Sebelas Maret, 2020)
The purpose of this research is to increase student learning outcomes boldly on energy source material in class IV by using Youtube learning media. The research conducted was Classroom Action Research (CAR) in two cycles. Each cycle consists of planning, action, observation, and reflection. Data collection techniques used were observations, tests, and documentation of teacher and student activities, as well as written tests of student learning outcomes. In the first cycle of students who completed by 36%. In the second cycle of students who completed by 85%. These results indicate that the use of YouTube learning media can increase the learning outcomes of energy source material boldly in fourth grade students at SD Negeri Nongkosawit 02 for the 2019/2020 academic year.